Representasi Ilokusi dalam Tradisi Mangupa pada Horja Godang Etnis Batak Angkola: Telaah Pragmatik - Dewes Agustina Naibaho; Warisman Sinaga; Jekmen Sinulingga; Flansius Tampubolon; Asriaty r Purba (Jurnal Pendidikan Bahasa, 2026)
This study aims to reveal the representation of illocutionary speech acts in the Mangupa tradition during the Horja Godang ceremony of the Batak Angkola community. Mangupa is a verbal expression of blessings and hopes delivered by traditional leaders within the sacred context of customary rituals. This research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation methods. Data analysis is based on Searle's theory of illocutionary acts, which includes five categories: representative, directive, expressive, commissive, and declarative. The findings show that the utterances in Mangupa contain various types of illocutionary acts functioning to guide, bless, and affirm social status within the community. These utterances not only carry linguistic meaning but also hold social and cultural power that reinforces the value system of the Batak Angkola people. Furthermore, the structure of Mangupa utterances is highly influenced by customary norms and the Dalihan Na Tolu principle. This study confirms that the Mangupa tradition is a complex form of indigenous communication practice that embodies noble values. It contributes to the development of culturally-based pragmatic studies and supports the preservation of Indonesia’s oral cultural heritage.